A combined supplementation of vitamin B12 and omega-3 fatty acids across two generations improves cardiometabolic variables in rats. Issue 9 (16th August 2016) - Khaire, Amrita; Rathod, Richa; Randhir, Karuna; Kale, Anvita; Joshi, Sadhana
Abstract : Our earlier studies indicate that micronutrients (vitamin B12, folic acid) and omega-3 fatty acids especially docosahexaenoic acid (DHA) are interlinked in one carbon cycle. Abstract : Our earlier studies indicate that micronutrients (vitamin B12, folic acid) and omega-3 fatty acids especially docosahexaenoic acid (DHA) are interlinked in one carbon cycle. The present study examines the effects of a sustained vitamin B12 deficiency/supplementation in the presence of omega-3 fatty acids across two generations on the pregnancy outcome and cardiometabolic profile [blood pressure, plasma lipid profile (cholesterol and triglycerides), plasma/liver fatty acid profile and hepatic lipid metabolism] in the second generation adult Wistar rat offspring. Two generations of animals were fed the following diets: control; vitamin B12 deficient; vitamin B12 supplemented; vitamin B12 deficient diet supplemented with omega-3 fatty acids; vitamin B12 and omega-3 fatty acid supplemented diets. Male offspring were sacrificed at 3 months of age. Vitamin B12 deficiency lowered the weight gain ( p < 0.01) during pregnancy, increased systolic ( p < 0.05) and diastolic ( p < 0.01) blood pressure, and lowered the levels of plasma/liver DHA ( p < 0.05 for both) but did not affect the lipid profile. Vitamin B12 supplementation showed weight gain, blood pressure and the fatty acid profile similar to the control. However, it increased ( p < 0.05) the levels of plasma triglycerides. Omega-3 fatty acid supplementation to the vitamin B12 deficient group lowered the weight gain although the levels of cardiometabolic variables were comparable to the control. Omega-3 fatty acid supplementation in the presence of vitamin B12 improved the pregnancy outcome and all cardio-metabolic variables. Our study highlights the adverse effects of sustained vitamin B12 deficiency across two generations on the pregnancy outcome, fatty acid profile and blood pressure while a combined supplementation of vitamin B12 and omega-3 fatty acids is beneficial.